2017
DOI: 10.1007/s13312-017-1104-4
|View full text |Cite
|
Sign up to set email alerts
|

Lack of research amongst undergraduate medical students in India: It’s time to act and act now

Abstract: Participation in research is important in producing doctors with an understanding of evidence-based medicine. Though a mandatory part in post-graduate medical course, research has largely been invisible from the under graduation medical course in India. Very few research opportunities are available at under graduate level. The reason behind this is lack of encouragement, lack of basic infrastructure, facilities and structured mentorship programs, no extra incentives to researchers and the long journey to get a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 13 publications
0
30
0
1
Order By: Relevance
“… 20 , 21 A published systematic review on attitudes of medical studies to medical leadership reported that one of the most important barriers to implementing research activities within medical schools is a lack of time given competing educational demands; the main cause cited by students in developing countries as their priority is in completing clinical studies. 7 , 22 …”
Section: Issues Behind Variability In Research Uptake Among Undergradmentioning
confidence: 99%
See 4 more Smart Citations
“… 20 , 21 A published systematic review on attitudes of medical studies to medical leadership reported that one of the most important barriers to implementing research activities within medical schools is a lack of time given competing educational demands; the main cause cited by students in developing countries as their priority is in completing clinical studies. 7 , 22 …”
Section: Issues Behind Variability In Research Uptake Among Undergradmentioning
confidence: 99%
“…19 , 30 On the other hand, if students had prior knowledge, they are more likely to pursue academic career, especially in developed countries compared to developing countries. 7 , 14 An interview-based study revealed that 64% compared to 48% of students who had prior research experience were willing to pursue in this field. 14 This study also identified that when three domains of self-determination theory were applied, well-supported compulsory research activities that incorporate group learning and elements of choice may promote motivation to do research and, potentially, careers in research, even in a research-naive student body.…”
Section: Knowledgementioning
confidence: 99%
See 3 more Smart Citations